Modern problems of reproduction of public health of the population - Bakhov Ivan; Boichenko Elina; Martynovych Nataly (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The study is based on the development of the basic provisions for the implementation of sustainable development, namely one of its goals: “Overcoming poverty in all its forms”, which were approved in 2015 at the UN Summit on Sustainable Development. Reproduction of the public health of the population is the basis of the mechanism for the prevention of poverty in the territories, presented in doctoral dissertation Martynovych Nataly. Also, modern problems of reproduction of public health of the population form the conceptual foundations of the applied state theme “Economic and legal support of the strategic development of newly formed territorial communities”. This topic was approved by the Decree of the Bureau of the Department of Economics of the National Academy of Sciences of Ukraine and is carried out by the staff of the department of problems of interregional cooperation of the Institute of Economic and Legal Research of the NAS of Ukraine Martynovych Nataly, Boichenko Elina. The purpose of the research is to determine by the empirical way modern problems of reproduction of public health of the population and the development of comprehensive measures to overcome them. The findings showed an integral assessment of the state of public health of the population was carried out, as a result of which it was established that only three-quarters of the population of Ukraine can be considered healthy. Empirically, an increase in the deficit of the average life expectancy of the population is determined, and the main reasons for such dynamics are also indicated. The proposed measures to promote an increase in the life expectancy of the population of the region.